Analisis Kebijakan Produk Dalam Perkembangan Pemasaran Global di Indonesia - Suhairi, Suhairi; Hidayat, Alfy; Yasmita, Hafsyah; Surya Sirait, Mentari Kinanti; Reitandi, Reitandi (Universitas Labuhanbatu, 2022)
Currently, the development of global markets and business has become a very rapid thing for humans to do. Business people certainly need to change their minds so they can follow the existing trends in order to be able to develop their business and corporate entities as a result of business developments in the current global era. If product policy issues are checked accurately and thoroughly, it will do well; otherwise, it would be a disaster. If a product can be produced and sold on a large scale, and accepted, then it is deemed technically feasible. So this research will focus on the study of product policy analysis in the development of global marketing in Indonesia.